The implementation of competitive intelligence tools and techniques in public service departments in South Africa to improve service delivery : a case study of the Department of Home Affairs - Snyman, M.E. (Martha Elizabeth) (University of Pretoria, 2013)
Thesis (DPhil)--University of Pretoria, 2009.